Endogenous cartel formation: Experimental evidence - Miguel A. Fonseca; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
In a Bertrand-oligopoly experiment, firms choose whether or not to engage in cartel-like communication and, if so, they may get fined by a cartel authority. We find that four-firm industries form cartels more often than duopolies because they gain less from a hysteresis effect after cartel disruption.
Keywords: C7; C9; L41; 330; cartels; collusion; communication; experiments; repeated games